Saturated Fatty Acid Intake Can Influence Increase in Plasminogen Activator Inhibitor-1 in Obese Adolescents - Masquio, D. C. L.; de Piano, A.; Campos, R. M. S.; Sanches, P. L.; Corgosinho, F. C.; Carnier, J.; Oyama, L. M.; do Nascimento, C. M. P. O.; de Mello, M. T.; Tufik, S.; Dâmaso, A. R. (Hormone and Metabolic Research, 2014)
The aim of this study was to verify if saturated fatty acid intake adjusted by tertiles can influence metabolic, inflammation, and plasminogen activator inhibitor-1 (PAI-1) in obese adolescents. Body mass, height, body mass index, waist circumference, blood pressure, and body composition of 108 obese adolescents were obtained. Fasting glucose, insulin, PAI-1, and CRP were determined. Insulin resistance was assessed by Homeostasis Model Assessment (HOMA-IR) and insulin sensitivity by Quantitative Insulin Sensitivity Check Index (QUICKI). Dietetic intake was estimated by a 3-day dietary record, and volunteers were divided according to consumption of saturated fatty acids: tertile 1 [Low Saturated Fatty Acid Intake (Low-SFA): ≤12.14 g], tertile 2 [Moderate Saturated Fatty Intake (Moderate SFA intake): 12.15–20.48 g], and tertile 3 [High Saturated Fatty Acid Intake (High-SFA Intake); >20.48 g]. Statistical analysis was performed using STATISTICA 7.0 software and the significance level was set at p<0.05. The most important finding in the present study is that Moderate and High-SFA intakes presented significantly higher values of PAI-1 than Low-SFA Intake. PAI-1 was positively associated with saturated fatty intake, waist circumference, mean blood pressure, and HOMA-IR. SFA intake was predictor of PAI-1 independent of body fat, HOMA-IR and total-cholesterol. In addition, PAI-1 was an independent predictor of blood pressure. HOMA-IR and QUICKI presented significantly higher and lower, respectively, in High-SFA compared to Moderate-SFA intake. High-SFA influenced cardiovascular disease risks, since it increased PAI-1 and insulin resistance, and decreased insulin sensibility, leading to vicious cycle among food ingestion, pro-thrombotic state, and cardiovascular risks in obese adolescents.
Keywords: obesity; saturated fatty intake; PAI-1; insulin resistance